O riso e a comicidade no Quixote - Ferreira, Patrícia Maria da Silva (2017)
The old criticism of Quixote ([1605] 2002), until the 1750s, formed the work as purely comic. With the arrival of the romantic interpretation, from the eighteenth century, Quixote went from a crazy burlesque to a utopian dreamer, and what was comic turned in to tragically. Even though there are different interpretations, in Quixote there is, with no doubt, a strong presence of comedy. This is especially notable for his parody structure, but, in addition, the Cervantine text causes laughter in several other ways. Therefore, our proposal focuses on the analysis of how this comic is caused. Much of what is written about the laughable in the Quixote identifies only the parody and the stylistic contractor as causers of the comedy of the work. This study, on the other hand, intends to link the Cervantine narrative to theories of laughter, in order to perform a work in which other ways of laughable present in the work will be evidenced. In addition, a historical panorama of laughter, from antiquity to the period of publication of the Quixote (seventeenth century), will be drawn up to provide support for a better understanding of the comic in Cervantes' masterpiece. Key words: Don Quixote. Comic. Laughable. Cervantes.